Agnieszka Gromkowska-Melosik, Educational tests. A study of the dynamics of selection and socialization, Adam Mickiewicz University Press, Poznań 2017, pp. 202 - Adamczewski, Jakub (Studia Edukacyjne, 2020)
Agnieszka Gromkowska-Melosik, Educational tests. A study of the dynamics of selection and socialization, Adam Mickiewicz University Press, Poznań 2017, pp. 202